Adapting Pedagogical Approaches in Model Islamic Educational Institutions: Balancing Contemporary Needs with Islamic Values - Jallow, Amadou F.; Jabbie, Alhassan (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2024)
AbstractThis paper examines the adaptation of pedagogical approaches in model Islamic educational institutions in The Gambia, focusing on the balance between contemporary educational needs and Islamic values. Through a comparative analysis of a selected institution in The Gambia, this study explores how the school incorporates innovative teaching strategies and contemporary curricula alongside traditional Islamic teachings using a single case study of the qualitative research approach. The findings were viewed through DuBow and Litzler’s (2019) Theory of Change (ToC). A thorough synthesis of the data, collected through semi-structured interviews with the school leader and teachers, revealed that model Islamic schools in the Gambia could integrate modern teaching methods and maintain their students’ Islamic values through preparation (planning), execution(implementation), risks, and outcomes (evaluative interventions). The findings from this paper highlight best practices and identify potential areas for improvement, offering insights into how a model Islamic educational institution can effectively navigate the demands of modern education without compromising its foundational Islamic values. The implications for policymakers, educators, and religious leaders underscore the importance of collaboration and flexibility in fostering educational environments that honor Islamic traditions and contemporary educational standards. AbstrakArtikel ini mengkaji adaptasi pendekatan pedagogis di institusi pendidikan Islam model di Gambia, dengan fokus pada keseimbangan antara kebutuhan pendidikan kontemporer dan nilai-nilai Islam. Melalui analisis komparatif pada salah satu institusi di Gambia, studi ini mengeksplorasi bagaimana sekolah tersebut mengintegrasikan strategi pengajaran inovatif dan kurikulum kontemporer bersama dengan pengajaran Islam tradisional menggunakan pendekatan studi kasus tunggal dalam penelitian kualitatif. Temuan dianalisis menggunakan Theory of Change (ToC) dari DuBow dan Litzler (2019). Sintesis data yang diperoleh melalui wawancara semi-terstruktur dengan pemimpin sekolah dan guru mengungkapkan bahwa sekolah Islam model di Gambia dapat mengintegrasikan metode pengajaran modern sekaligus mempertahankan nilai-nilai Islam siswa melalui tahapan persiapan (perencanaan), pelaksanaan (implementasi), risiko, dan hasil (intervensi evaluatif). Temuan dari artikel ini menyoroti praktik terbaik dan mengidentifikasi potensi area yang dapat ditingkatkan, serta memberikan wawasan tentang bagaimana institusi pendidikan Islam model dapat secara efektif menavigasi tuntutan pendidikan modern tanpa mengorbankan nilai-nilai Islam yang mendasarinya. Implikasinya bagi pembuat kebijakan, pendidik, dan pemimpin agama menekankan pentingnya kolaborasi dan fleksibilitas dalam menciptakan lingkungan pendidikan yang menghormati tradisi Islam sekaligus memenuhi standar pendidikan kontemporer. How to Cite: . Jallow, A. F., & Jabbie, A. (2024). Adapting Pedagogical Approaches in Model Islamic Educational Institutions: Balancing Contemporary Needs with Islamic Values. TARBIYA: Journal of Education in Muslim Society, 11(2), 115-134. doi:10.15408/tjems.v11i2.40965.